A Comparative Analysis of the Investment Characteristics of Alternative Gold Assets. (March 2014) - Pullen, Tim; Benson, Karen; Faff, Robert
<x xml:space="preserve">Abstract</x> Employing daily data over the period 1987–2010, we examine the diversifying, hedging and safe haven properties of gold bullion, gold stocks, gold mutual funds, and gold exchange traded funds (ETFs). First, with regard to gold bullion, we document a clear and strong hedging role over a mere diversifying capability. Second, our results highlight that gold stocks, gold mutual funds, and gold ETFs tend to be diversifiers. Third, both gold bullion and gold ETFs show support for the safe haven property. However, gold stocks and gold mutual funds display very little evidence of the safe haven characteristic. Consequently, investors who are keen on securing the safe haven features of gold investment cannot generally rely on gold stocks or mutual funds. Instead, they need to take positions directly in bullion or gold ETFs.